Training on HOTS-Based Question Development to Enhance Learning Assessment Skills of Teachers at MIN 5 Magelang - Siti Nafi'ah; Handara Elitasari; Muhammad Rafi Prakosa (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Most teachers at MIN 5 Magelang have difficulty creating HOTS (high order thinking skills) questions due to limited conceptual understanding, lack of specialized training, limited time, and scarce learning resources. These factors make it challenging for teachers to design questions with a high cognitive level that align with Bloom's taxonomy and the learning context. Learning assessment skills are among the essential competencies teachers must possess. Compiling HOTS questions is a critical skill for teachers in the 21st century to prepare students for future challenges. This community service employs a unique service learning method by applying concentrated experience, reflective observation, abstract conceptualization, and active experimentation. This approach emphasizes collaboration and real-life experience, enabling teachers not only to learn theory but also to practice together. The results show an increase in learning assessment skills in compiling HOTS questions based on various indicators, including understanding HOTS questions, their characteristics, question levels, and Bloom's taxonomy.